Promoción de la salud ambiental con niñas y niños en escuelas de Córdoba: el mapeo colectivo como herramienta de participación - Eandi, Mariana Andrea (Universidad Nacional del Litoral, 2021)
This work, prepared by an extension team of teachers and students from the National University of Córdoba, arises from the concern of a group of women organized around horticultural production and exposure to pesticides in the green belt of the city of Córdoba. The project was designed and carried out together with the local primary school and its educational community. This article proposes: a) To present an experience of approaching integral environmental health with girls and boys in a school environment; b) Reflect on the usefulness of Collective Mapping as a tool for making visible and exchanging knowledge, experiences and problem–situations in everyday life. It is postulated that the process carried out is useful for the collective management of comprehensive environmental health, together with girls, boys, their families and teachers.